A comparative study of the Indonesia-Malaysia border regions - Sulistyarini Sulistyarini; Iwan Ramadhan; Jagad Aditya Dewantara; Efriani Efriani; Wibowo Heru Prasetiyo (Universitas Negeri Yogyakarta, 2026)
This study aims to investigate the socio-cultural, economic, and educational aspects of border communities between Indonesia and Malaysia, with a focus on the Malay and Dayak ethnic groups in Paloh (Sambas Regency) and Jagoi Babang (Bengkayang Regency). Persistent disparities in welfare, educational quality, and national integration in Indonesia’s border regions have weakened nationalism and increased socio-economic dependence on Malaysia. On the border, civic education plays a crucial role in strengthening Indonesian nationalism, despite the community’s economic dependence on Malaysia. Through flag ceremonies, character education, and the integration of local wisdom into the curriculum, schools function as the final bastion of nationalism, safeguarding the national identity of the younger generation in the face of economic inequality and transnational influences. Using a qualitative approach that integrates ethnographic and etnopedagogic methods, data were collected through participatory observation, semi-structured interviews, and document analysis. The findings indicate that Indonesian border communities experience a dual identity, marked by both symbolic loyalty to Indonesia and pragmatic attachment to Sarawak, Malaysia. Economic disparities between the two countries, especially in access to infrastructure, education, and labour markets, have heightened social dependency and eroded Indonesia’s national identity. However, the integration of local wisdom and etnopedagogic practices in education in both countries has proven effective in strengthening cultural resilience, social cohesion, and national consciousness among students. Cultural rituals such as Gawai Dayak serve as transnational spaces of solidarity that both connect and differentiate the two nations.